2018
DOI: 10.14238/pi58.6.2018.274-9
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms associated with type 1 diabetes mellitus

Abstract: Background Type 1 diabetes mellitus (T1DM) is an organ-specific autoimmune disease characterized by T cell-mediated destruction of pancreatic islets. The genetic factors involved consist of at least five vulnerability genes:  HLA, INS, CTLA-4, PTPN22, and IL2RA/CD25. Objective To investigate for associations of PTPN22-1123 G>C SNP and CTLA-4 +49A/G polymorphisms with T1DM. Methods Case and control groups underwent CTLA-4 +49A/G gene examination from June to December 2017, using polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
(20 reference statements)
0
4
1
Order By: Relevance
“…A study in Palembang reported the CTLA-4 49 A/G gene polymorphism to be prevalent in 36% T1Dof M subjects; the frequency of G and encylele was 71.6%. 24 Unlike our study, Tanhapour et al showed that the correlation between CTLA-4 CT60 A/G polymorphism and autoimmune disorders is inconclusive. 20 …”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…A study in Palembang reported the CTLA-4 49 A/G gene polymorphism to be prevalent in 36% T1Dof M subjects; the frequency of G and encylele was 71.6%. 24 Unlike our study, Tanhapour et al showed that the correlation between CTLA-4 CT60 A/G polymorphism and autoimmune disorders is inconclusive. 20 …”
Section: Discussioncontrasting
confidence: 93%
“…The frequency of polymorphism of CTLA-4 49 A/G in Palembang ethnic was 46.7%. 24 A significant risk of CTLA-4 49 A/G, otherwise reported in the Indian and African populations, has been reported in the Middle East and Caucasian populations. 20 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There are various causes of T1DM, such as genetic risk factors including β-pancreatic cell destruction induced by T-cell [ 2 , 11 , 12 ]. In 2008, Ikegami et al.…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports of the 1858T allele being linked to T1DM in several countries, including Italy, Germany, Spain, Ukraine and France [ 13 ]. This topic has been studied since 12 years ago [ 12 , 17 , 18 ]. However, PTPN22 studies in Indonesia is limited.…”
Section: Introductionmentioning
confidence: 99%